The Welfare of Syrian Refugees : Evidence from Jordan and Lebanon - Verme, Paolo (Washington, DC: World Bank, 2015)
The book focuses on the largest refugee crisis of our time: the Syrian refugee crisis. It exploits a wealth of survey and registry data on Syrian refugees living in Jordan and Lebanon to assess their poverty and vulnerability status, understand the predictors of these statuses, evaluate the performance of existing policies toward refugees, and determine the potential for alternative policies. Findings point to a complex situation. In the absence of humanitarian assistance, poverty is extremely high among refugees. Current policies including cash transfers and food vouchers are effective in reducing poverty but they remain short of providing economic inclusion and self-reliance of refugees. A shift toward economic inclusion and self-reliance would require a different humanitarian and development paradigm, one that focuses on growth policies for areas affected by refugees where the target population is constituted by refugees and hosting populations alike.